The role of lymphoid tissue SPARC in the pathogenesis and response to treatment of multiple myeloma - Aly, Nesreen Amer Ramadan; Rizk, Samia; Aboul Enein, Azza; El Desoukey, Nermeen; Zawam, Hamdy; Ahmed, Manzoor; El Shikh, Mohey Eldin; Pitzalis, Costantino (Frontiers in Oncology, 2022)
Background Despite the significant progress in the treatment of multiple myeloma (MM), the disease remains untreatable and its cure is still an unmet clinical need. Neoplastic transformation in MM is initiated in the germinal centers (GCs) of secondary lymphoid tissue (SLT) where B cells experience extensive somatic hypermutation induced by follicular dendritic cells (FDCs) and T-cell signals. Objective We reason that secreted protein acidic and rich in cysteine (SPARC), a common stromal motif expressed by FDCs at the origin (SLTs) and the destination (BM) of MM, plays a role in the pathogenesis of MM, and, here, we sought to investigate this role. Methods There were 107 BM biopsies from 57 MM patients (taken at different time points) together with 13 control specimens assessed for SPARC gene and protein expression and compared with tonsillar tissues. In addition, regulation of myeloma-promoting genes by SPARC-secreting FDCs was assessed in in vitro GC reactions (GCRs). Results SPARC gene expression was confirmed in both human primary (BM) and secondary (tonsils) lymphoid tissues, and the expression was significantly higher in the BM. Sparc was detectable in the BM and tonsillar lysates, co-localized with the FDC markers in both tissues, and stimulation of FDCs in vitro induced significantly higher levels of SPARC expression than unstimulated controls. In addition, SPARC inversely correlated with BM PC infiltration, ISS staging, and ECOG performance of the MM patients, and in vitro addition of FDCs to lymphocytes inhibited the expression of several oncogenes associated with malignant transformation of PCs. Conclusion FDC-SPARC inhibits several myelomagenic gene expression and inversely correlates with PC infiltration and MM progression. Therapeutic induction of SPARC expression through combinations of the current MM drugs, repositioning of non-MM drugs, or novel drug discovery could pave the way to better control MM in clinically severe and drug-resistant patients.